Research on Anxiety of Learning Chinese as a Second or Foreign Language in and Outside Mainland China: A Systematic Review of the Literature 1999–2020 - Yao, Shuangyun; Zhang, Dujuan; Shen, Qian (Frontiers in Psychology, 2022)
This paper reviews research on anxiety of learning Chinese as a second or foreign language (CSL/CFL) in and outside mainland China. This review involves 52 Chinese language articles identified in leading journals from the Chinese National Knowledge Infrastructure (CNKI) database (中国知网) and 42 English language articles from the Web of Science and ERIC database published during the period of 1999 to 2020. By adopting bibliometric analysis and content analysis, this study compares the topical issues and methodological trends of research on CSL/CFL learning anxiety published in leading Chinese and international journals. The review found that, compared with mainland Chinese scholars, international researchers examined a broader range of topical issues from multidimensional perspectives. While most Chinese empirical studies are dominated by the quantitative approach, qualitative methods such as classroom observations and in-depth interviews were also widely adopted by international researchers. The analysis also revealed that although Chinese scholars had drawn on well-established theories and concepts originating from foreign language anxiety (FLA) research, their role in CSL/CFL anxiety research is limited and peripheral. Consequently, we conclude this review with recommendations that encourage mainland Chinese researchers to be well informed by the updated theoretical perspective and methodological approaches such as the utilization of social network analysis and the integration of Information Communications Technology in language education.